An investigation into the influence of the "Cape Malay" child's cultural heritage upon his taste in appreciating music, with a proposed adaptation of the music curricula in South African schools to reflect a possible application of "Cape Malay" music therein - Desai, Desmond (College of Music, 2023)
This investigation of a repertory of music, grew out of a need to find a link between the societal structures created, and the activity of a group of people for whom they are intended. Music is a universal phenomenon but has definite cultural boundaries. Ever since the author became a student at the University of Cape Town, he came under the deep impression of differing cultural activities. This dissertation is a result of cultural differences observed by him from childhood, concerning a group of people, who are termed 'Cape Malay', for the lack of a more appropriate term. 'Cape Ma lay' music, which refers to the who le repertory of moppies, ghommaliedjies, nederlandsliedere, ouliedere, £udjies and djiekers of the 'Cape Malay', was observed by him as a way of life of many South Africans. This is not always realised, and it is the hope of the author that educational authorities would try to recognise not only this 'Malay' musica l culture, but also make provision for its inclusion in the syllabus. The basic philosophy which the author has tried to convey, is that education should link up with the pupil's social environment. Allied with this, is an attempt by the author to develop and awareness of 'Malay' music amongst those South Africans who might not be aware of this repertory of music, which is unique in the world. The reading material is extensive, as may be ascerta ined from the lengthy bibliography at the end of this dissertation. Unfortunately, it is not nearly complete. Two very important sources are regrettably not included: A pre liminary thesis by Erica Mugglestone completed for a master's degree at Monash Un iversity in Australia, relating to the topic of this dissertation; and van Warmelo's work, which relates to 'Cape Malay ' music, and from